Comparision of ultrasonography with direct radiography and aspiration for the confirmation of nasogastric tube placement among intubated patients in the emergency servise: A prospective,single-blind,cross-sectional study - Ucel Cayhan, Duygu; Akif Ustuner, Mehmet; Parlak, Ismet (Annals of Medical Research, 2021)
Aim: The position of the nasogastric tube should be confirmed after its initial insertion and prior to repeated use. The present study makes a prospective comparison of the efficacy of ultrasonography, aspiration and direct radiography in confirming nasogastric tube placement among intubated patients.Materials and Methods: This prospective, single-blind and cross-sectional study included 45 (16 female and 29 male) patients over the age of 18 who were intubated and had a nasogastric tube inserted at the Emergency Service between 01.03.2017 and 30.08.2017. For the confirmation of NGT placement, both gastric aspiration and gastric auscultation were performed by the primary physician who initially inserted the NGT. The abdominal USG was performed by an emergency physician who had performed the procedure 20 times previously. Results: The ultrasound had a sensitivity of 92%, a specificity of 100%, a positive predictive value of 100% and a negative predictive value of 50%. The direct radiography had a sensitivity of 57%, a specificity of 100%, a positive predictive value of 100% and a negative predictive value of 14%. The aspiration method, in turn, had a sensitivity of 78.57%, a specificity of 66.67%, a positive predictive value of 97.06% and a negative predictive value of 18.18% as a means of NGT placement confirmation.Conclusion: Bedside ultrasonography is more effective than the aspiration method and direct radiography for the placement confirmation of NGT inserted into intubated patients in the emergency service.
Keywords: Aspiration method; direct radiography; emergency service; intubated patients; Nasogastric tube; ultrasound